RETRACTED: Biodegradation of Endocrine-Disrupting Chemicals and Residual Organic Pollutants of Pulp and Paper Mill Effluent by Biostimulation - Chandra, Ram; Sharma, Pooja; Yadav, Sangeeta; Tripathi, Sonam (Frontiers in Microbiology, 2018)
Effluent discharged from the pulp and paper industry contains various refractory and androgenic compounds, even after secondary treatment by activated processes. Detailed knowledge is not yet available regarding the properties of organic pollutants and methods for their bioremediation. This study focused on detecting residual organic pollutants of pulp and paper mill effluent after biological treatment and assessing their degradability by biostimulation. The major compounds identified in the effluent were 2,3,6-trimethylphenol, 2-methoxyphenol (guaiacol), 2,6-dimethoxyphenol (syringol), methoxycinnamic acid, pentadecane, octadecanoic acid, trimethylsilyl ester, cyclotetracosane, 5,8-dimethoxy-6-methyl-2,4-bis(phenylmethyl)napthalen-1-ol, and 1,2-benzendicarboxylic acid diisononyl ester. Most of these compounds are classified as endocrine-disrupting chemicals and environmental toxicants. Some compounds are lignin monomers that are metabolic products from secondary treatment of the discharged effluent. This indicated that the existing industrial process could not further degrade the effluent. Supplementation by carbon (glucose 1.0%) and nitrogen (peptone 0.5%) bio-stimulated the degradation process. The degraded sample after biostimulation showed either disappearance or generation of metabolic products under optimized conditions, i.e., a stirring rate of 150 rpm and temperature of 37 ± 1°C after 3 and 6 days of bacterial incubation. Isolated potential autochthonous bacteria were identified as Klebsiella pneumoniae IITRCP04 (KU715839), Enterobacter cloacae strain IITRCP11 (KU715840), Enterobacter cloacae IITRCP14 (KU715841), and Acinetobacter pittii strain IITRCP19 (KU715842). Lactic acid, benzoic acid, and vanillin, resulting from residual chlorolignin compounds, were generated as potential value-added products during the detoxification of effluent in the biostimulation process, supporting the commercial importance of this process.